Distance between valvular leaflet and coronary ostium predicting risk of coronary obstruction during TAVR. (December 2021) - Oh, Jun-Hyok; Kobayashi, Yuhei; Kang, Guson; Nishi, Takeshi; Willemink, Martin J.; Fearon, William F.; Fischbein, Michael; Fleischmann, Dominik; Yeung, Alan C.; Kim, Juyong Brian
Graphical abstract: Abstract: Background: The aim of this study was to evaluate the role of the distance between the aortic valve in projected position to the coronary ostium to determine risk of coronary artery obstruction after transcatheter aortic valve replacement (TAVR). Methods: An Expected Leaflet-to-ostium Distance (ELOD) was obtained on pre-TAVR planning computed tomography by subtracting leaflet thickness and the distances from the center to the annular rim at annulus level and from the center to the coronary ostium at mid-ostial level. Variables were compared between patients with and without coronary obstruction and the level of association between variables was assessed using log odds ratio (OR). Results: A total of 177 patients with 353 coronary arteries was analyzed. Mean annulus diameters (22.8 ± 2.8 mm and 23.4 ± 1.0 mm, p > 0.05) and mean sinus of Valsalva (SOV) diameters (31.2 ± 3.6 mm and 31.9 ± 3.6 mm, p > 0.05) were similar between patients with lower and higher coronary heights, respectively. There were three coronary obstruction cases. ELOD ≤ 2 mm in combination with leaflet length longer than mid-ostial height allowed for discrimination of cases with and without coronary obstruction. There was a significant association between coronary obstruction event and ELOD ≤ 2 mm (log OR = 6.180, p < 0.001). Conclusions: Our study showed that a combination of ELOD < 2 mm and a longer leaflet length than mid-ostial height may be associated with increased risk for coronary obstruction during TAVR.